Neighbor-based probabilistic rebroadcast routing protocol for reducing routing overhead in mobile ad hoc networks - Harum, Norharyati; Mas'ud, Mohd Zaki; Mat Ariff, Nor Azman; Hamid, Erman; Bahaman, Nazrulazhar (Dr. John M. Jun, 2021)
In Mobile Ad-Hoc Network (MANET) Application, routing protocol is essential to ensure successful data transmission to all nodes. Ad-hoc On-demand Distance Vector (AODV) Protocol is a reactive routing protocol that is mostly used in MANET applications. However, the protocol causes Route Request (RREQ) message flooding issue due to the broadcasting method at the route request stage to find a path to a particular destination, where the RREQ will be rebroadcast if no Request Response (RREP) message is received. A scalable neighbor-based routing (SNBR) protocol was then proposed to overcome the issue. In the SNBR protocol, the RREQ message is only rebroadcast if the number of neighbor nodes less than a certain fix number, known as drop factor. However, since a network always have a dynamic characteristic with a dynamic number of neighbor nodes, the fix drop factor in SNBR protocol could not provide an optimal flooding problem solution in a low dense network environment, where the RREQ message is continuously rebroadcast RREQ message until reach the fix drop factor. To overcome this problem, a new broadcasting method as Dynamic SNBR (DSNBR) is proposed, where the drop factor is determined based on current number of neighbor nodes. This method rebroadcast the extra RREQ messages based on the determined dynamic drop factor. The performance of the proposed DSNBR is evaluated using NS2 and compared with the performance of the existing protocol; AODV and SNBR. Simulation results show that the new routing protocol reduces the routing request overhead, energy consumption, MAC Collision and enhances end-to-end delay, network coverage ratio as a result of reducing the extra route request messages.